Special cases in order statistics for the alternative parametrization of the Generalized Power Function Distribution. Issue 3 (4th May 2018) - Al Mutairi, Alya O.; Volodin, Andrei
ABSTRACT: This paper investigates the order statistics based on the moment-generating function for the Generalized Power Function Distribution for the two different forms of this distribution. In this paper, we continue our investigation on the distribution of order statistics assuming that the original sample of size n is taken from a population that follows the Generalized Power Function Distribution. Two different forms of the Generalized Power Function Distribution with its special cases are presented and some order statistics related to these different forms are discussed. The main technique is the consideration of the moment-generating function.